An extension to EMTPL - Cobo, María Laura (2002)
The development of languages allowing a proper handling of time is important in many areas of computer science because the capability to deal with the notions of change and time are essential to solve their problems. In the development of EMTPL [CA99a] we focused the research work in making the languages useful in the area of databases, where some problems demand the possibility to represent and use temporal information. We achieve that goal, although we managed the negation in a way that causes the lost of some properties of the underlying logic. This logic was deeply studied and it is one of the most famous metric temporal logics [Pri67a]. The main idea of this work is to extend EMTPL by the addition of a new operator, and also grant the negation with its logic meaning.